Person-Organization Fit: It's Relationships with Job Attitudes and Behaviors of Turkish Academicians - TUGAL, Fatma Nur; KILIC, Kemal Can (International Review of Management and Marketing, 2015)
Congruence between the employees and the organization which is often called the person-organization (P-O) fit is the main theme of this article. Previous research about person-organization fit (Cable and DeRue 2002; Hoffman and Woehr 2006; Lauver and Kristof-Brown 2001; Nelson and Billsberry, 2007; O'Reilly and Chatman 1986; Sekiguchi 2004) revealed that a high level of congruence creates positive outcomes for both employees and organizations. In this context, this study attempts to explore the relationships between the P-O fit and job attitudes and behaviors of Turkish academics (e.g., organizational commitment, organizational citizenship behaviors, and the intention to quit of Turkish academicians). In order to test the hypotheses empirically; data was collected from academicians of aStateUniversitylocated inTurkey. After the reliability, correlation and regression analysis, the study was concluded by discussing its implications, limitations, and future research concerning the person-organization fit. Keywords: person-organization fit; organizational commitment; organizational citizenship behaviors; intention to quit; Turkish Academicians; Turkey JEL Classification: M10